Reading between Blurred Lines: The complexity of interpretation. (December 2017) - Handforth, Rachel; Paterson, Laura L.; Coffey-Glover, Laura; Mills, Sara
Abstract: This article uses thematic qualitative analysis and techniques from corpus linguistics to interrogate the way that listeners interpret and make sense of Blurred Lines. The song was controversial upon its release as many listeners felt that it implied that even if women said they did not want sex, in fact, they did. Such issues of sexual consent are a key issue for feminist analysis, particularly within current debates about 'rape culture'. We investigated listeners' interpretations of the song, distributing an online questionnaire to over 1000 respondents. We found that most listeners either interpreted the song as relating to sexual consent and took offence, or felt that it was simply representative of the genre, and found the song unproblematic. However, a number of listeners expressed conflict in relation to the song, enjoying it musically but finding the lyrics particularly problematic. Our analysis investigates the language that respondents used to negotiate their relationships with the different elements of the song.